Burnout syndrome in undergraduate medical students in brazil: a review of the brazilian context - Nassar, Leonardo Maso (2021)
Burnout Syndrome is a psychological syndrome that arises in the context of stress related to work, affecting mainly health professionals, especially physicians. Objective of the study: integrative literature review in order to map the available literature to provide an overview of research on Burnout Syndrome in medical students of undergraduate courses at Brazilian colleges. Methodology: the methodology used for the review was developed by the Joanna Briggs Institute (JBI), applying the mnemonic Population, Concept and Context (PCC) for a Scoping Review. Results: eight studies developed in fifteen different Brazilian states and one state in the USA were selected. Conclusion: the results indicate that Burnout in medical students is a present and widespread problem in Brazil, requiring adjustments in national medical training.